PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA PAMFLET DILENGKAPI LKS QUESTION BOX TERHADAP HASIL BELAJAR SISWA DI SMPN 1 MAMBORO - Rambu Patti, Marsiane; Makaborang, Yohana; Rambu Hada Enda, Riwa (Jurnal Biogenerasi, 2025)
This study aims to determine the effect of the cooperative learning model Make a Match assisted by pamphlet media and supplemented with Question Box student worksheets (LKS) on the learning outcomes of eighth-grade students at SMP Negeri 1 Mamboro. The research employed a quantitative experimental method using a posttest-only control group design. The sample consisted of 44 students, with 21 students in the control class and 23 in the experimental class. Data were collected through a learning outcome test. Data analysis using the t-test revealed a significant difference between the control and experimental classes, with a significance value of < 0.05. These results indicate that the implementation of the Make a Match learning model assisted by pamphlet media and Question Box worksheets has a positive effect on students’ learning outcomes.